2022
DOI: 10.1186/s13052-022-01308-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of TikTok among children and adolescents with Eating Disorders: experience in a third-level public Italian center during the SARS-CoV-2 pandemic

Abstract: Background Recent research has documented the potential associations existing between the use of social media (SM) and the occurrence/development and treatment of Eating Disorders (ED). However, the literature directly addressing the use of SM TikTok among children and adolescents with ED is still scarce. Methods In January–February 2021, during the second Italian national lockdown due to the SARS-CoV-2 pandemic, an anonymous paper survey was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This information could deepen our understanding of the influence of social media dance on learning, understanding, and subsequently performing full-body movements in social and communicative settings. Further, it is important to consider the effect of social media engagement on young people's development, given that emerging research reports engagement with social media to be both positive (e.g., enhanced multicultural experience, cultural intelligence, individual creativity) 50 and negative (i.e., disordered body image, low self-esteem) 51 for young people's development. An opportunity clearly exists for further research to enhance our understanding of the extent to which engagement in art-based trends (i.e., dance, as opposed to dangerous behaviours) might impact its consumers.…”
Section: Individual Experiences With the Arts Influence Familiarity A...mentioning
confidence: 99%
“…This information could deepen our understanding of the influence of social media dance on learning, understanding, and subsequently performing full-body movements in social and communicative settings. Further, it is important to consider the effect of social media engagement on young people's development, given that emerging research reports engagement with social media to be both positive (e.g., enhanced multicultural experience, cultural intelligence, individual creativity) 50 and negative (i.e., disordered body image, low self-esteem) 51 for young people's development. An opportunity clearly exists for further research to enhance our understanding of the extent to which engagement in art-based trends (i.e., dance, as opposed to dangerous behaviours) might impact its consumers.…”
Section: Individual Experiences With the Arts Influence Familiarity A...mentioning
confidence: 99%
“…Although previous studies have examined eating disorder content on other social media platforms, such as Twitter, 10,11 Instagram, 12 and Tumblr, 13 there has been little systematic study about eating disorder content on TikTok. Studies extended to TikTok have highlighted both the benefits 6 and risks 14,15 associated with exposure to eating disorder content and communities on the platform.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have examined eating disorder content on other social media platforms, such as Twitter, 10 , 11 Instagram, 12 and Tumblr, 13 there has been little systematic study about eating disorder content on TikTok. Studies extended to TikTok have highlighted both the benefits 6 and risks 14 , 15 associated with exposure to eating disorder content and communities on the platform. However, as studies have not fully evaluated the accuracy of the content to which users are exposed, a more comprehensive understanding of the information environment on TikTok is needed to bridge these studies’ findings and identify the platform and content characteristics that enable or impede the dissemination of misleading information.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in Liang Ji Xue's opinion, teenagers can develop their self-esteem well by themselves [6]. In the research on children during the pandemic period, researchers found that 59.0% of teenagers reduced self-esteem during that period [7]. Most of the research in this field discusses the importance of self-esteem in teenagers.…”
Section: Introductionmentioning
confidence: 99%